ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENDIDIKAN, PENGANGGURAN DAN KEMISKINAN TERHADAP MIGRASI TKI KELUAR NEGERI - Oli, Maria Frianti Yaninsa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Economic growth is an indicator in determining the success of a country. Differences in characteristics between provinces in Indonesia and especially in East Nusa Tenggara Province have differences in natural, economic, and social resources. Judging from the level of economic growth that is still low, when compared to other provinces in Indonesia, the province of NTT is ranked 33 out of 34 provinces in Indonesia. In addition, the level of education in NTT Province is still considered low, which can be seen from the average length of schooling of residents in NTT only up to grade 1 (one) junior high school. As well as other problems such as the number of unemployed being quite high, and the high number of poverty are ranked 3 (three) in Indonesia. One of the conditions is the lack of availability of jobs that makes residents in the Province of NTT choose to work abroad to become migrant workers. This study aims to determine and analyze the effect of Economic Growth, Education, Unemployment, and Poverty on the Migration of Indonesian Migrant Workers abroad in the population in the Province of NTT 2015-2020. This study uses panel data analysis and secondary data, using explanatory research. The result of this study is that the variables of Economic Growth, Education, and Poverty have a significant effect on the Migration variable. While the Unemployment variable has no significant effect on the Migration variable. Economic growth is an indicator in determining the success of a country. Differences in characteristics between provinces in Indonesia and especially in East Nusa Tenggara Province have differences in natural, economic, and social resources. Judging from the level of economic growth that is still low, when compared to other provinces in Indonesia, the province of NTT is ranked 33 out of 34 provinces in Indonesia. In addition, the level of education in NTT Province is still considered low, which can be seen from the average length of schooling of residents in NTT only up to grade 1 (one) junior high school. As well as other problems such as the number of unemployed being quite high, and the high number of poverty are ranked 3 (three) in Indonesia. One of the conditions is the lack of availability of jobs that makes residents in the Province of NTT choose to work abroad to become migrant workers. This study aims to determine and analyze the effect of Economic Growth, Education, Unemployment, and Poverty on the Migration of Indonesian Migrant Workers abroad in the population in the Province of NTT 2015-2020. This study uses panel data analysis and secondary data, using explanatory research. The result of this study is that the variables of Economic Growth, Education, and Poverty have a significant effect on the Migration variable. While the Unemployment variable has no significant effect on the Migration variable.